Uji Model Fisik Water Treatment Bentuk Pipa dengan Media Aerasi Baling-Baling - Surya Budi Lesmana , Indah Nurfathin (Semesta Teknika, 2012)
Both water and health are inter-connected things. Water is used for many daily needs. In Universitas Muhammadiyah Yogyakarta, water needs are quite big, such as for bathroom needs, laboratory, mosque and other places. Because of that, water quality in campus need to be examined in order to fulfill requirement of Indonesia Health Ministry (KepMenKes No. 907/2002). That requirement is about water conditions and supervision. This study aimed to analyze the ability of water treatment equipment used by doing analysis of Fe and DO parameters.